Heating with Biomass in the United Kingdom: Lessons from New Zealand. (March 2017) - Mitchell, E.J.S.; Coulson, G.; Butt, E.W.; Forster, P.M.; Jones, J.M.; Williams, A.
Abstract: In this study we review the current status of residential solid fuel (RSF) use in the UK and compare it with New Zealand, which has had severe wintertime air quality issues for many years that is directly attributable to domestic wood burning in heating stoves. Results showed that RSF contributed to more than 40 μg m −3 PM10 and 10 μg m −3 BC in some suburban locations of New Zealand in 2006, with significant air quality and climate impacts. Models predict RSF consumption in New Zealand to decrease slightly from 7 PJ to 6 PJ between 1990 and 2030, whereas consumption in the UK increases by a factor of 14. Emissions are highest from heating stoves and fireplaces, and their calculated contribution to radiative forcing in the UK increases by 23% between 2010 and 2030, with black carbon accounting for more than three quarters of the total warming effect. By 2030, the residential sector accounts for 44% of total BC emissions in the UK and far exceeds emissions from the traffic sector. Finally, a unique bottom-up emissions inventory was produced for both countries using the latest national survey and census data for the year 2013/14. Fuel- and technology-specific emissions factors were compared between multiple inventories including GAINS, the IPCC, the EMEP/EEA and the NAEI. In the UK, it was found that wood consumption in stoves was within 30% of the GAINS inventory, but consumption in fireplaces was substantially higher and fossil fuel consumption is more than twice the GAINS estimate. As a result, emissions were generally a factor of 2–3 higher for biomass and 2–6 higher for coal. In New Zealand, coal and lignite consumption in stoves is within 24% of the GAINS inventory estimate, but wood consumption is more than 7 times the GAINS estimate. As a result, emissions were generally a factor of 1–2 higher for coal and several times higher for wood. The results of this study indicate that emissions from residential heating stoves and fireplaces may be underestimated in climate models. Emissions are increasing rapidly in the UK which may result in severe wintertime air quality reductions, as seen in New Zealand, and contribute to climate warming unless controls are implemented such as the Ecodesign emissions limits. Graphical abstract: A delivery of wood logs to a home in South Island, New Zealand. Highlights: Residential wood combustion (RWC) currently accounts for >10% of renewable energy and >50% of renewable heat generation in the UK. Models predict UK RWC to increase by a factor of 14 between 1990 and 2030, with heating stoves and fireplaces dominating. Wood consumption per person in New Zealand is twice that of the UK, with significant air quality and climate impacts. Black carbon has surpassed carbon dioxide to become the most important component of RSF radiative forcing.